2000
DOI: 10.1007/pl00006672
|View full text |Cite
|
Sign up to set email alerts
|

B lymphocyte pathology in human colorectal cancer. Experimental and clinical therapeutic effects of partial B cell depletion

Abstract: Accumulating data are showing that the humoral immune response against tumors could favor tumor progression. However, no B lymphocyte pathology has been reported in cancer. Using anti-IgM Ab we nonspecifically depleted B cells in tumor-bearing mice, a treatment that resulted in significant reduction of tumor burden. We analyzed the B lymphocyte phenotype of abdominal lymph nodes and peripheral blood from advanced colon cancer patients by flow cytometry, and compared the B cell phenotype with that found in samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 29 publications
1
89
1
1
Order By: Relevance
“…The observed persistence of B cells in lymphoid tissues after RTX treatment, has been reported by others before (8,13,15,(22)(23)(24)(25)(26). However, in contrast to our finding of unaffected numbers of LN B cells, these studies described at least some degree of B cell reduction in synovial tissue, spleen or LNs.…”
Section: Cd4supporting
confidence: 80%
“…The observed persistence of B cells in lymphoid tissues after RTX treatment, has been reported by others before (8,13,15,(22)(23)(24)(25)(26). However, in contrast to our finding of unaffected numbers of LN B cells, these studies described at least some degree of B cell reduction in synovial tissue, spleen or LNs.…”
Section: Cd4supporting
confidence: 80%
“…In a syngeneic mouse model, pro-active B cell depletion of tumor-bearing mice led to reduction in tumor burden. 41 It is of interest to examine whether this phenomenon could be applied to a variety of tumors. Rituximab, a humanized anti-CD20 antibody extensively used for treating B cell lymphomas produces a state of B-cell depletion lasting several months and could be used for the purpose of adult B cell depletion in humans.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies comparing wild-type and B cell-deficient mice found that B cells inhibit T cell-mediated regression of established tumors (32,33), as well as T cell responses to cancer vaccines (34)(35)(36). B cells can impair the priming of CD8 + CTL responses by CD4 + T cells and instead promote nonprotective humoral immune responses (37).…”
Section: B Cells In Cancermentioning
confidence: 99%